Case Study : Nursing Care for Schizophrenia Patients with Low Self-Esteem at RSJ Prof HB. Saanin Padang - Yudistira Afconneri; Elza Putri Aprilia; Yulastri; Yulvi Hardoni (Jurnal Kesehatan Cendikia Jenius, 2024)
Low self-esteem is a negative symptom in schizophrenia patients, where clients experience negative feelings toward themselves and others, leading to feelings of worthlessness and hopelessness. Without intervention, this condition can result in social isolation. This study aims to provide nursing care for schizophrenia patients with low self-esteem issues at RSJ Prof. HB. Saanin Padang in 2024. The research method used is a single case descriptive study with a case study approach. Nursing care was conducted from May 29 to June 4, involving one participant with low self-esteem issues. Data was collected through interviews, direct measurement, and observation. The assessment results indicated that the client frequently felt worthless, with a diagnosis of chronic low self-esteem. The intervention included behavior management over six days through activities such as making the bed, sweeping, and folding blankets. After implementation, there was an improvement in self-esteem, eye contact, and the ability to choose activities. Conclusion : Clients with low self-esteem benefit from social support. Recommended : The hospital is expected to maintain the existing interventions, and future researchers are encouraged to focus their implementation strategies on schizophrenia clients with low self-esteem.